POST-TRAUMATIC GROWTH IN THE QURAN: Psychological Insights from the Story of Prophet Ayyub - Khodijah, Siti; Arif, Muhammad; Fadzil, Huda Mohd; Johari, Aisyah (Ulul Albab: Jurnal Studi Islam, 2025)
Post-Traumatic Growth (PTG), developed by Tedeschi and Calhoun, describes the positive transformations that may emerge following profound suffering or trauma. These include strengthened interpersonal relationships, enhanced personal strength, a renewed appreciation for life, openness to new possibilities, and spiritual development. Although PTG has been widely examined in contemporary psychology, its application within Quranic exegesis remains limited. Employing a qualitative approach through library research, this study analyzes the story of Prophet Ayyub AS in Q.S. al-Anbiyâ [21]: 83-84 and Q.S. Sâd [38]: 41-44 through a comparative exegesis (tafsîr muqâran), drawing on classical (al-T{abarî), medieval (Ibn Kathîr), and contemporary (Quraish Shihab) commentaries. The comparative analysis, with a thematic focus on suffering and recovery, is mapped onto five domains of PTG. It shows how Ayyub AS’s ordeal catalyzes meaning-making, moral refinement, relational restoration, and spiritual strengthening. It operationalizes spiritual resilience as s{abr (patient steadfastness) and tawakkul (trustful reliance on God) that stabilize cognition and affect, sustain moral commitment (istiqamah), and convert affliction into disciplined, hopeful action. Spiritual resilience thus functions both as a mediator and an outcome of PTG, integrating divine mercy with human initiative. Hence, the study presents a Quranic-based framework for resilience and psychological transformation, interpreting suffering not merely as a test of endurance but as a process of growth, meaning-making, and spiritual elevation. It contributes to contemporary Quranic scholarship by integrating exegetical perspectives across classical, medieval, and modern periods and contextualizing them within the framework of PTG, thereby enriching the interdisciplinary dialogue between Islamic exegesis and modern psychology.